Gender Issues and Violence in School: a literature review (Research, Society and Development, 2022)
This article is an invitation to reflect on the multiple faces of gender violence in the various spaces of society. We start from the idea that essentialist conceptions naturalize and justify the differences between those involved, which have been ingredients for the various manifestations of this phenomenon, such as in formal teaching spaces. Thus, the main objective of this article is to analyze gender violence from research published in scientific articles through the database of the Scientific Electronic Online Library (SCIELO) in the period 2012 - 2021.This research is of a bibliographic nature and made use of the literature review, whose data were analyzed using a qualitative approach. In the development of work, we used selection criteria for the publications analyzed, such as, guiding question, descriptors (violence, gender and school), full text articles in Portuguese with theoretical, methodological, bibliographic and field research assumptions, in the different thematic areas, published in the period mentioned above, inserted in journals of qualis A and B. In the results, we found that gender violence permeates the lives of people in the school context and in other environments, of all age groups, regardless of class, sex and race. However, the indicators are more frequent for subjects with low economic scores; non-white (women and men, heterosexual or not, of all age groups) and low schooling.